The Dual Role of Collaborative Culture in Leadership-Team Performance Dynamics: A Quantitative Study of Public Sector Institutions - Amin, Shofia; Widiastuti, Fitri; Sumarni, Sumarni; Shahnaz, Muthia (Universitas Bangka Belitung, 2025)
This study examines the mediating and moderating effects of collaborative culture on the relationship between leadership behavior and team performance in modern organizations, specifically focusing on how collaborative culture elements such as knowledge sharing, skill exchange, interpersonal relationships, and synergistic attitudes can serve as strategies for enhancing team performance. Employing a quantitative methodology, data was collected through online questionnaires from 121 employees of government institutions in Jambi and analyzed using Structural Equation Modeling (SEM). The findings revealed that leadership behavior significantly and positively influences both team performance and collaborative culture, while collaborative culture, though showing no direct significant effect on team performance, functions as both a mediator and moderator in the leadership behavior-team performance relationship. Although the study's generalizability may be limited due to its specific focus on public sector institutions, this study strengthens the research gap on the dual role of collaborative culture which is still rarely discussed in the context of the Indonesian public sector. The practical implications of this finding can be a reference for organizational leaders to develop team effectiveness and achieve strategic goals through strengthening collaborative culture in public sector management.